Genome-Wide Identification and Functional Characterization of β-Agarases in Vibrio astriarenae Strain HN897 - Liu, Yupeng; Jin, Xingkun; Wu, Chao; Zhu, Xinyuan; Liu, Min; Call, Douglas R.; Zhao, Zhe (Frontiers in Microbiology, 2020)
The genus Vibrio is a genetically and metabolically versatile group of heterotrophic bacteria that are important contributors to carbon cycling within marine and estuarine ecosystems. HN897, a Vibrio strain isolated from the coastal seawater of South China, was shown to be agarolytic and capable of catabolizing D-galactose. Herein, we used Illumina and PacBio sequencing to assemble the whole genome sequence for the strain HN897, which was comprised of two circular chromosomes (Vas1 and Vas2). Genome-wide phylogenetic analysis with 140 other Vibrio sequences firmly placed the strain HN897 into the Marisflavi clade, with Vibrio astriarenae strain C7 being the closest relative. Of all types of carbohydrate-active enzyme classes, glycoside hydrolases (GH) were the most common in the HN897 genome. These included eight GHs identified as putative β-agarases belonging to GH16 and GH50 families in equal proportions. Synteny analysis showed that GH16 and GH50 genes were tandemly arrayed on two different chromosomes consistent with gene duplication. Gene knockout and complementation studies and phenotypic assays confirmed that Vas1_1339, a GH16_16 subfamily gene, exhibits an agarolytic phenotype of the strain. Collectively, these findings explained the agar-decomposing of strain HN897, but also provided valuable resources to gain more detailed insights into the evolution and physiological capability of the strain HN897, which was a presumptive member of the species V. astriarenae.